Training on the maximization of product quality and layout at Cuanki Kang Raffie Bandung - Resi Juariah Susanto; Anton Mulyono Azis (Universitas Ahmad Dahlan, Yogyakarta, 2021)
Cuanki is a kind of soup, often referred to as Bandung meatballs. Because this business can be done at home, the community service program is carried out, aiming to increase its sales turnover by maximizing the layout and good quality of Cuanki Kang Raffie in Bandung City. This community service program takes the form of training and mentoring for business actors to see the operational management scientific briefing results at the beginning of the activity. This program is one of the efforts to improve the capabilities and skills of small businesses to increase their business and lead to an increase in total income. Problems that business actors often face include not emphasizing good layout and paying attention to maximum quality so that the impact on not seeing an inappropriate layout and less than optimal product quality. It also affects operational planning in the next period. Moreover, what is done in this service is in the form of providing knowledge and improvements in terms of layout or layout. This dedication makes the work process faster, and there are not many obstacles or interruptions so that the quality of the product is better maintained. The object of this community service is Cuanki Kang Raffie, whose address is Jl. Pasir Layung Bandung.